Can environmentally friendly technology help China to achieve a carbon neutrality target by 2060? An asymmetrical based study in China - Nurgazina, Zhanar; Guo, Qingbin; Ali, Uzair; Sharif, Arshian; Khan, Zaid Ashiq; Kartal, Mustafa Tevfik; Kilic Depren, Serpil (SPRINGER HEIDELBERG, 2023)
Climate change-related environmental challenges are prompting an increasing number of countries to set carbon-neutral targets. Since 2007, China has pursued numerous initiatives to attain carbon neutrality by 2060, including increasing the percentage of non-fossil energy, developing zero-emission and low-emission technologies, and taking actions that reduce CO2 emissions or boost carbon sinks. As a result, utilizing quarterly data from 2008/Q1 to 2021/Q4, and applying the nonlinear autoregressive distributed lag (NARDL) approach, this study evaluates the effectiveness of the measures taken by China to improve the ecological situation. The results of the study show that the measures enacted to reduce CO2 emissions did not accomplish their ultimate purpose. Specifically: (i) high-speed railways and new energy vehicles do not improve the environment in the long run; (ii) investments and patents in the energy sector, as well as low-carbon sources, will degrade the environment; (iii) only investments in the treatment of environmental pollution will improve the ecological situation. Various policy implications are suggested based on the empirical results in order to attain environmental sustainability.
Keywords: CO2 emissions; High-speed railway; New energy vehicles; Investments; Patents; China; RENEWABLE ENERGY-CONSUMPTION; CO2 EMISSIONS ANALYSIS; ELECTRIC VEHICLES; DIOXIDE EMISSIONS; NUCLEAR-ENERGY; TRANSPORTATION; DETERMINANTS; COUNTRIES; QUALITY; MODEL; Environmental Sciences & Ecology